46 Classic or new echocardiographic parameters in the evaluation of the right ventricular function after tricuspid valve surgery?. (17th January 2020) - Segura Rodriguez, D; Torres-Quintero, L; Rodriguez-Torres, D J; Moreno-Escobar, E; Garcia-Orta, R
Abstract: Background: Tricuspid valve regurgitation(TR) is frequent in patients undergoing to valvular heart disease surgery, particularly joined to mitral valve surgery. Classically, it was considered that left valve disease surgery would regress the TR without requiring any surgery on it, which has not been confirmed during follow-up. There is no consensus about which tricuspid lesions need to be operated neither which is the best surgical technique. Purpose: In this study, we have evaluated the right ventricle(RV) function by advanced transthoracic echocardiography before to surgery and three months later. Methods: Prospective cohort including 43 patients with valve surgical indication and some degree of tricuspid insufficiency. An advanced echocardiographic study was performed to determine the RV function measured by the following variables: basal diameter, Tricuspid Annular Plane Systolic Excursion(TAPSE), end-systolic RV area, fractional area change(FAC), systolic tricuspid valve lateral annular velocities by tissue Doppler(s') and global longitudinal strain(GLS). Variables were tested to normality with Kolmogorov-Smirnoff test. Wilcoxon test was performed in order to compare measures previous and after surgery. Results: 43 patients were analysed. Mean age 64.7 ± 8.3 years, 31(72.1%) were female, 36 patients(83.7%) with functional TR which was associated to a left valvulopathy in 31(72.4%)cases. 17 patients(39.5%) had severe TR, 19 patients(44.2%) had moderate TR and 7 patients(16.3%) had mild TR. Twelve patients(27.9%) had isolated tricuspid surgery. The most frequent TR surgery was simple annuloplasty with 27 patients (62.8%). The classic RV echocardiographic parameters at initial evaluation and three months after surgery showed the following values respectively:Mean RV basal diameter was 48.3 ± 8.0mm vs. 41.7 ± 4.7 mm(p < 0.001), TAPSE was 19.0 ± 4.4mm vs. 15.7 ± 3.4mm (p < 0.001), peak systolic lateral annular velocity (s") was 0.12 ± 0.11cm/s vs. 0.11± 0.14cm/s(p = 0.001), FAC was 39.2 ± 13.2% vs. 38.2 ± 11.8%(p = Not significant), end-systolic RV area was 15.8 ± 10.2cm² vs. 14.4 ± 4.0cm²(p = Not significant). Nonetheless, there had not worsening in RV function based on myocardial deformation, with no significant differences between RV GLS(-20.0 ± 5.4% vs. -19.6 ± 4.9%; p = Not significant). Conclusions: In our sample, 3 months post-surgery, the classic echocardiographic parameters based on the translational motion of the heart showed worsening of RV function. The parameters based on myocardial deformation do not show changes in RV function post-surgery, being better indicators of RV function in recently operated patients. These differences could be explain because tricuspid surgery is focus on the annulus that affects its motion while it does not affect to the global RV myocardial function evaluated by GLS.